Spatial performance of location-based alerts in France. (November 2020) - Bopp, Esteban; Douvinet, Johnny
Abstract: This study experiments a method for estimating and mapping the alerting potential of two Location-Based Alerting Solutions (LBAS): messaging techniques (cell broadcast, CBC, or location-based SMS, LB-SMS) and the smartphone push notification. Experiments have been evaluated over metropolitan France, a heterogeneously populated and risky area, considering that individuals are located at home. The rate of alertable individuals, calculated at the municipal level, show very strong potential of CBC/LB-SMS. 94.21% of individuals can be alertable using CBC/LB-SMS and 74.15% using the smartphone push notification. There is a very strong homogeneity in the performance of LBAS at the national level, but also local weaknesses exist. Mapping this potential of performance contributes to the discussion about the use of LBAS in France and paves the way for a broader assessment of the effectiveness of alerting solutions in order to propose a multi-channel system that will consider the territorial characteristics. Graphical abstract: Image 1 Highlights: The performance of Location-Based Alerting System (LBAS) is estimated in France. 94.21% of individuals would be alertable using cell broadcast or LB-SMS. 74.15% of individuals would be alertable using smartphone push notification system. LBAS make alerting spatially equitable at the national level even if low clusters exist. LBAS are less performant in rural, mountainous and sparsely populated areas.